Navigating authority and legitimacy when 'outsider' volunteers co-produce emergency management services. (1st January 2021) - McLennan, Blythe J.; Whittaker, Joshua; Kruger, Tarn; Handmer, John
ABSTRACT: This paper examines the thorny issue of authority and legitimacy in relation to 'outsider' emergency volunteering within the context of the community resilience policy agenda. Outsider emergency volunteering is any volunteering that: (a) aims to assist communities in any aspect of disaster preparedness, response, relief and recovery, and (b) is not registered with or under the direction of a formally recognised emergency management organisation (EMO). Hence, it does not have clear grounds to establish its authority and legitimacy within the formal authorising environment of the emergency management sector. The paper draws on co-production theory to examine how three important challenges for establishing authority and legitimacy were navigated in four Australian cases of co-production involving outsider emergency volunteering. Given the rise of resilience in disaster policy and the changing nature of volunteering in modern society, the very formalised and defined foundations of authority and legitimacy in emergency management will need to soften and expand to become more networked and distributed. The four cases described here shed some light on what softer and expanded foundations for authority and legitimacy can look like and the processes that can support them in the emergency management context.